2014
DOI: 10.1158/1078-0432.ccr-14-0361
|View full text |Cite
|
Sign up to set email alerts
|

Circulating pEGFR Is a Candidate Response Biomarker of Cetuximab Therapy in Colorectal Cancer

Abstract: Purpose: The lack of secreted biomarkers measurable by noninvasive tests hampers the development of effective targeted therapies against cancer. Our hypothesis is that cetuximab (an anti-EGFR mAb) induces a specific secretome in colorectal cancer cells that could be exploited for biomarker discovery.Experimental Design: Considering the strong correlation between mutated KRAS and a lack of response to cetuximab therapy, we addressed whether performing secretome-based proteomics on isogenic colorectal cancer cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Some of these unconventionally secreted proteins have a welldefined intracellular function (6). We have previously shown that the unconventional secretion of the EGFR correlates with the response of colorectal cancer patients to the therapeutic antibody cetuximab (8). Agreeing with our observations, proteins classically located intracellularly such as HSP90, tRNA synthetases, and HMGB1 have recently been identified in the extracellular space performing alternative functions related to cancer (9)(10)(11).…”
Section: Introductionsupporting
confidence: 76%
“…Some of these unconventionally secreted proteins have a welldefined intracellular function (6). We have previously shown that the unconventional secretion of the EGFR correlates with the response of colorectal cancer patients to the therapeutic antibody cetuximab (8). Agreeing with our observations, proteins classically located intracellularly such as HSP90, tRNA synthetases, and HMGB1 have recently been identified in the extracellular space performing alternative functions related to cancer (9)(10)(11).…”
Section: Introductionsupporting
confidence: 76%
“…Interestingly, we observed that two compounds with limited effects in 2D culture displayed enhanced activity in the 3D setting (PX‐866 and AZD6482); this raises the possibility that certain PI3K inhibitors may be underestimated based on adherent culture results alone. This needs careful exploration given that 3D disease models can be more reflective of the drug sensitivity profile found in patients (Katsila et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…They noted that during cetuximab treatment, pEGFR levels increased in patients who responded well to treatment, did not evolve in patients with stabilisation of the disease, and decreased in patients with disease progression. The authors subsequently validated this hypothesis by measuring the secretome in 3D cultures obtained from several lines of SW48 colorectal cancer cells with different sensitivities to cetuximab [60]. This latter study is a good example of a proteomic study performed on human samples and validated by in vitro cell models, hence promoting the use of 3D cell cultures obtained directly from patient samples to pre-test the treatment.…”
Section: Proteomics For Biomarker Researchmentioning
confidence: 97%